Clinical utility of liver biopsies in dogs undergoing splenectomy. (9th October 2020) - Clarke, E.; Levien, A. S.; Bennett, R. A.; Perry, S.; Daniel, G.
Abstract : Objective: To determine the prevalence of neoplasia detected on liver biopsy obtained at the time of splenectomy in dogs with splenic masses. Materials and Methods: Retrospective study of medical records of dogs with splenic masses from which liver biopsies were taken following splenectomy. Results: Malignant splenic neoplasia was detected in 50 of 113 (44.2%) of the dogs undergoing splenectomy. Neoplastic liver disease was detected on biopsy from 1 of 40 (2.5%) dogs with a grossly normal liver and from 20 of 69 (28.9%) dogs with a grossly abnormal liver. Dogs with a grossly abnormal liver had a 16 times (95% CI: 2.5‐170) higher chance of being diagnosed with liver neoplasia on biopsy. Haemoabdomen was also associated with an increased likelihood of liver neoplasia on biopsy at the time of splenectomy. Clinical Significance: A liver biopsy taken from grossly normal liver is a low‐yield diagnostic test but liver biopsy is recommended following splenectomy if the liver appears abnormal at surgery.